Analisis faktor-faktor yang mempengaruhi keberlanjutan mata pencaharian petambak garam di madura menggunakan metode MICMAC - Silvia Rosalinda; Raden Faridz; Umi Purwandari; Hamzah Fansuri (AGROINTEK, 2022)
Madura Island is the largest salt-producing area with a potential land area of 15 thousand ha. In 2018 the total salt production of Madura reached 768,136.22 tons or 39.45% of national production. Its large production contribution has an impact on the coastal communities of Madura, namely: in addition to providing employment opportunities also increase income. But the potential nationally has not significantly decreased salt imports. This is evident that still, high imports in 2020 reached 2.61 million tons. Because domestic production is still not enough to provide its needs, especially salt industrial needs. The causes are very complex and occur in almost every salt-producing region including Madura are: low productivity, process technology is still traditional, salt quality is low, dependence on weather, erratic salt prices, narrow land area, lack of empowerment of salt farmers, capital, education, supply chain, and infrastructure. Solving it requires priority and known related relationships, and systematic analytical thinking is needed. Therefore the purpose of this study is to illustrate how the interrelationships between variables in the system, and their key factors. One of the methods used is the MICMAC (Matrix of Crossed Impact Multiplications Applied to a Classification) method. Through this method, it will be illustrated more clearly the strength of the relationship between factors and the key to a more structured and specific solution. This research was conducted in Sampang Regency, Pamekasan Regency, and Sumenep Regency. Based on the results of the MICMAC analysis it is known that the key factors that play an important role and influence on other variables are capital, distribution, and technology variables. While variables that have very high dependency tend to be influenced by other variables are price, capital, and market expansion